1995
DOI: 10.1111/j.1532-5415.1995.tb07341.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence Associated with Dementia

Abstract: Urinary incontinence is common in patients with dementia and is more prevalent in demented than in nondemented older individuals. It occurs with equal or greater frequency in males than in females, and this contrasts with the female preponderance in community-based, general older populations. Since the etiology of incontinence in dementia is multifactorial, a comprehensive assessment of factors within and outside the lower urinary tract is essential. A careful clinical evaluation is sufficient to guide treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 83 publications
2
77
1
7
Order By: Relevance
“…Šveicarijos slaugos namuose atlikto tyrimo duomenimis, šlapimo nelaikymas buvo daž-nesnis tiriamiesiems, turėjusiems atminties ir judėjimo sutrikimų, o šlapimo nelaikymą mažino protinės ir fizinės veiklos pratimai (22). Demencija sergantys pagyvenusio amžiaus pacientai dažnai nelaikė šlapimo ir tokia situacija kėlė paciento globėjų stresą, slaugos ekonominių kaštų didėjimą (23,24).…”
Section: Odeta Kučikienė Vita Lesauskaitė Jūratė Macijauskienė Godunclassified
“…Šveicarijos slaugos namuose atlikto tyrimo duomenimis, šlapimo nelaikymas buvo daž-nesnis tiriamiesiems, turėjusiems atminties ir judėjimo sutrikimų, o šlapimo nelaikymą mažino protinės ir fizinės veiklos pratimai (22). Demencija sergantys pagyvenusio amžiaus pacientai dažnai nelaikė šlapimo ir tokia situacija kėlė paciento globėjų stresą, slaugos ekonominių kaštų didėjimą (23,24).…”
Section: Odeta Kučikienė Vita Lesauskaitė Jūratė Macijauskienė Godunclassified
“…It was therefore thought that DO explains UI in dementia patients. Different underlying mechanisms of UI are also expected however in this patient population [83,84].…”
Section: Dementiamentioning
confidence: 99%
“…Studies showed that in patients with cognitive impairment, cerebral dysfunction affects the frontal lobe control on the micturition reflex. This leads to involuntary detrusor contractions [83]. Involuntary detrusor contraction is interpreted in urodynamic studies as DO.…”
Section: Dementiamentioning
confidence: 99%
“…A full UDS for the elderly with dementia is difficult to perform and is invasive. Therefore, it should be considered only if other treatment modalities failed and the results have direct influence on treatment choices and outcome [3,23].…”
Section: Evaluation Of Uimentioning
confidence: 99%
“…It is a common problem among the elderly, estimated to affect about 11-21% of community dwelling elderly in an Italian study and up to 77% of the residents in nursing homes [1,2]. Among the elderly with dementia, the prevalence is higher with 22% of the community dwelling elderly and 84% of nursing home residents reported to have UI [3]. Even though urinary incontinence is a common problem among the elderly, it should not be considered as synonymous with the normal ageing process.…”
Section: Introductionmentioning
confidence: 99%